Volatility Composite Index and Exchange Rates in Indonesia: EGARCH/TARCH Model for VAR Estimation - Lia Amaliawiati; Gusni Gusni; Eristy Minda Utami; Farida Nursjanti; Siti Komariah (Ekonomis: Journal of Economics and Business, 2023)
Composite index and exchange rate are important indicators that represent a country's economic performance, where there is a relationship between the two. In this study, the ideal model to capture the volatility of the composite index and exchange rate will be determined. to investigate the dynamic dependency relationship between the composite index and the exchange rate, first use a Vector Autoregressive (VAR) model. The best model in describing the volatility of the composite index is the EGARCH model while the exchange rate is using the TARCH model. According to research, there is an asymmetry relationship between the volatility of stock returns and the exchange rate, which means that the market will react to bad news more quickly than good news. According to the VAR model, the present volatility is influenced by the volatility of the prior period and there is a one-way causal relationship between the composite index and the exchange rate.